Artificial Intelligence Animation in English Learning: Innovation in the Merdeka Curriculum Implementation - Muhamad Alfi Khoiruman; Mohd. Rafi Riyawi; Galih Satriyo (AL-ISHLAH: Jurnal Pendidikan, 2025)
Conventional teaching methods often lack interactivity and fail to address diverse learning needs, resulting in reduced student engagement. This study investigates the use of AI-based animation as an innovative educational tool to enhance student motivation, participation, and comprehension, in alignment with the Merdeka Curriculum’s focus on student-centered and flexible learning approaches. A qualitative research design was employed, involving semi-structured interviews with educators and students, as well as participant observations in classroom settings. The implementation of an AI animation tool was assessed using user engagement metrics and thematic analysis of feedback from both students and teachers. Initial classroom trials indicated a 25% increase in student participation when AI animations were integrated into lessons, compared to traditional teaching methods. Furthermore, 80% of students reported that the AI-based animations made learning more enjoyable and accessible, citing improved understanding and sustained interest in classroom activities. The findings highlight the effectiveness of AI-based animations in fostering active learning and engagement. This approach supports the Merdeka Curriculum’s principles of autonomy, collaboration, and adaptive pedagogy. By catering to diverse student needs and promoting a more dynamic classroom environment, AI-driven tools offer promising pathways for future educational innovation.